THE EFFECT OF rGH ADDITION ON ARTIFICIAL FEED ON HOVEN’S CARP GROWTH, Leptobarbus hoevenii (Bleker, 1851) - Nur Selawati; Indra Gumay Yudha; Deny Sapto Chondro Utomo (University of Lampung, 2019)
Hoven’s carp is one of the potential fish in Indonesia to be developed. But due to its slow growth, making people not cultivating it. This research aimed to study the effect of using rGH and determine the best dosage on growth of hoven’s carp. Hoven’s carp used were 70 - 90 mm in size and 5 - 6 g in weight 4 months old. Hoven’s carp used are 10 fish in each pond This study used a completely randomized design with 4 treatments and 3 replications. The treatment was A (without administration of rGH), B (administration of rGH 1 mg/kg of feed), C (administration of rGH 2 mg/kg of feed), and D (administration of rGH 3 mg/kg of feed). Parameters observed consisted of growth absolute length, the growth of absolute weight, SR, FCR, and protein retention. The results showed that the effect on hoven’s carp growth of rGH and best dose in this study is in treatment B (administration of rGH 2 mg/kg of feed)